Development of Injectable Formulation of 4’-O-benzyloxycarbonyl-etoposide Derivative Based on Human Serum Albumin for the Chemotherapy of Breast Cancer - T. S. Kovshova; S. A. Boiko; M. A. Merkulova; N. S. Osipova; N. I. Moiseeva; Ju. A. Malinovskaya; S. N. Mantrov; S. E. Gelperina (Разработка и регистрация лекарственных средств, 2023)
Introduction. One of the promising strategies for the development of injectable formulations of poorly water-soluble drugs is the preparation of their nanosuspensions stabilized with albumin. A well-known example of the successful implementation of this technology is Abraxane® (nanoparticle albumin-bound paclitaxel). In the present study, this approach is used for the development of the injectable formulation of a hydrophobic etoposide prodrug.Aim. Development of the injectable formulation of a novel 4'-О-benzyloxycarbonyl derivative of etoposide (ETP-cbz) based on human serum albumin and evaluation of its cytotoxicity against breast carcinoma cells (BC).Materials and methods. The structure of ETP-cbz was confirmed by NMR spectroscopy and elemental analysis; log P was calculated in silico using Molinspiration Cheminformatics. The ETP-cbz-HSA nanoparticles were prepared by high pressure homogenization. The particle size, size distribution, and disintegration concentration were evaluated by dynamic light scattering (DLS) and atomic force microscopy (AFM). The contents of ETP-cbz and albumin in the formulation were determined by HPLC. The conversion ETP-cbz-HSA to etoposide was studied in a model medium in the presence of esterase. The cytotoxicity of ETP-cbz-HSA compared to etoposide and free ETP-cbz was assessed on BC cells (HBL-100 and MCF-7) using a colorimetric MTT assay.Results and discussion. ETP-cbz exhibited higher hydrophobicity as compared to the etoposide (log P 2.42 vs 0.7, respectively). Due to easy cleavage of the carbonate bond in the presence of esterase, ETP-cbz can be considered an etoposide prodrug. The ETP-cbz-containing HSA nanoparticles prepared by a high-pressure homogenization technique had the particle size of 110 ± 9 nm (DLS) and a low disintegration concentration of 3.0 ± 0.1 μg/mL. The drug content was 1.75 mg/mL. The nanoformulation demonstrated high cytotoxic activity in vitro against MCF-7 and HBL-100 cells that was comparable to the activity of substances etoposide and ETP-cbz.Conclusion. The obtained nanoformulation of etoposide prodrug based on albumin, suitable for injection, showed high cytotoxicity against breast cancer cells in vitro and deserves further study to assess the possibility of its use in breast cancer chemotherapy.